16.52% Efficiency All‐Polymer Solar Cells with High Tolerance of the Photoactive Layer Thickness. Issue 20 (17th April 2022) - Zhang, Wenqing; Sun, Chenkai; Angunawela, Indunil; Meng, Lei; Qin, Shucheng; Zhou, Liuyang; Li, Shaman; Zhuo, Hongmei; Yang, Guang; Zhang, Zhi‐Guo; Ade, Harald; Li, Yongfang
Abstract: All‐polymer solar cells (all‐PSCs) have drawn growing attention and achieved tremendous progress recently, but their power conversion efficiency (PCE) still lags behind small‐molecule‐acceptor (SMA)‐based PSCs due to the relative difficulty on morphology control of polymer photoactive blends. Here, low‐cost PTQ10 is introduced as a second polymer donor (a third component) into the PM6:PY‐IT blend to finely tune the energy‐level matching and microscopic morphology of the polymer blend photoactive layer. The addition of PTQ10 decreases the π–π stacking distance, and increases the π–π stacking coherence length and the ordered face‐on molecular packing orientation, which improves the charge separation and transport in the photoactive layer. Moreover, the deeper highest occupied molecular orbital energy level of the PTQ10 polymer donor than PM6 leads to higher open‐circuit voltage of the ternary all‐PSCs. As a result, a PCE of 16.52% is achieved for ternary all‐PSCs, which is one of the highest PCEs for all‐PSCs. In addition, the ternary devices exhibit a high tolerance of the photoactive layer thickness with high PCEs of 15.27% and 13.91% at photoactive layer thickness of ≈205 and ≈306 nm, respectively, which are the highest PCEs so far for all‐PSCs with a thick photoactive layer. Abstract : A 16.52% efficiency all‐polymer solar cell is achieved by morphology control of the photoactive layer through adding a low‐cost polymer donor, PTQ10, into the PM6:PY‐IT blend. Meanwhile, ternary devices exhibit a high tolerance of the photoactive layer thickness, with high power conversion efficiencies of 15.27% and 13.91% at photoactive layer thicknesses of ≈205 and ≈306 nm, respectively.